The Effectiveness of Remote Interaction in the Medical and Psychological Rehabilitation of Patients with Somatic Manifestations of Anxiety and Depressive Post-COVID Disorders - Burdeinyi, Andrii; Khaustova, Olena; Stashenko, Stanislav (Psychosomatic Medicine and General Practice, 2025)
The COVID-19 pandemic posed a significant challenge to the global healthcare system, resulting in not only physical but also profound psychological consequences. Its impact on the mental health of the population has been unprecedented, as many individuals faced negative emotions such as fear of infection, anxiety for loved ones, uncertainty about the future, and depression caused by social isolation. The constant stress triggered by these factors has significantly affected the autonomic nervous system, leading to the development of psychosomatic and somatic symptoms. Research indicates that a considerable portion of patients develop somatic symptom disorders (SSD) after recovering from COVID-19. According to DSM-5 criteria, 64% of patients met the diagnosis for SSD, exhibiting a wide range of symptoms such as chronic fatigue, muscle pain, headaches, and sleep disturbances. Additionally, 90% of patients experienced symptoms of chronic fatigue syndrome, severely diminishing their quality of life. Furthermore, 32% of individuals screened positive for mood and anxiety disorders, including depressive episodes, generalized anxiety, and panic attacks. These somatic symptoms not only exacerbate patients' physical conditions but also lead to significant psychological distress. Patients often feel confused and unsure of how to manage their condition, intensifying feelings of helplessness. Under such circumstances, integrating medical and psychological approaches to treating post-COVID disorders becomes crucial. A comprehensive approach, encompassing medical care, psychological counseling, and rehabilitation, enables the creation of an effective treatment plan tailored to the individual needs of each patient. The overall prevalence of post-COVID syndrome is approximately 80%. Although symptom intensity gradually diminishes over time, many patients continue to experience symptoms that remain higher than those observed in the general population even months after recovery. Cognitive-behavioral therapy (CBT) has proven particularly effective in treating such disorders, significantly reducing symptoms of SSD, depression, and anxiety. This form of psychotherapy helps patients learn to manage their emotions, understand the connection between thoughts, feelings, and behaviors, and develop new strategies for adapting to stress. The role of telemedicine, especially during the pandemic and the ongoing war in Ukraine, deserves special attention. Telemedicine has emerged as one of the key tools for supporting patients. The availability of rehabilitation programs through video conferencing, mobile apps, and other online resources has significantly enhanced the interaction between healthcare providers and patients. These tools have enabled effective support for emotional well-being, reduced symptom burden, and mitigated the risks associated with social isolation. Practical experience underscores the necessity of a multidisciplinary approach in treating post-COVID disorders. Specifically, medical-psychological rehabilitation programs that integrate tele-rehabilitation have become a pivotal step in the evolution of modern clinical practice. These programs contribute not only to the treatment but also to the prevention of psychosomatic disorders, creating a new standard of care. They empower patients to restore their physical health and improve their quality of life, laying a strong foundation for future well-being. Keywords: COVID-19, post-COVID syndrome, anxiety, depression, proactive psychosomatic medicine, telemedicine, telepsychology, quality of life, mental health